Pengaruh partisipasi penyusunan anggaran, kejelasan sasaran angaran, struktur desentraslisasi, akuntabilitas publik dan pengawasan fungsional terhadap kinerja manajerial pemerintah daerah - Anim Rahmayati (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2019)
This study aims to analyze the effect of budgeting participation, clarity of budget targets, decentralization structure, public accountability and functional supervision of managerial performance in Dinas Dinas in Wonogiri District. The research method used in this study is quantitative research using primary data. Primary data was obtained by distributing questionnaires to respondents, namely head of department, head of finance, and head of field at the agencies in Wonogiri Regency, amounting to 87 respondents. The data analysis technique uses multiple linear regression analysis. The results showed that budgetary participation, clarity of budget targets, decentralized structure and public accountability had an effect on managerial performance in Dinas-Dinas in Wonogiri district. While functional supervision has no effect on managerial performance in Dinas-Dinas in Wonogiri District. Keywords: managerial performance, budgeting participation, clarity of budget goals, decentralized structure, public accountability, functional supervision.